KANDUNGAN POLIFENOL DAN AKTIVITAS ANTIOKSIDAN TEH DAUN JAMBU BIJI (Psidium guajava L) - Citra Cintami Dusun; G. S. Suhartati Djarkasi; Thelma D.; Jean Tuju (COCOS, 2017)
ABSTRACTTea consumed is not only derived from tea plants, but can also come from fruits, spices, or other ingredients that are brewed. Guava is one of the potential crop to be used as tea, which is found in Indonesia. Guava leaf content is tannin, olive oil, flavonoids, carotene, vitamin B1, B2, B3, B6 and vitamin C (Ajizah, 2004; Ismail et al, 2012 in Rizqina, 2014). This research aims to determine the total content of phenols, flavonoids, total tannins, water content, and antioxidant activity of guava leaf tea, and to evaluate panelist preferences level on guava leaf tea.The experimental design used in this study was a complete Randomized Design (RAL) in 2 factorials, with 3 replications: Factor A Level of guava leaf location: A1. Location of leaf to 1 to 4, A2. The location of the leaf to 5 to 8, A3. The location of the leaf to 9 to 12. Factor B the size of guava leaf: B1. Leaf cashew flakes, B2. Powdered guava leaves. Each treatment was repeated as much as 3x to obtain 18 sample samples. Then tested, total phenol, flavonoids, tannins, water content, antioxidant activity using DPPH method on 18 samples. Then analyzed using analysis method of Variant (ANOVA). Result Of the highest total phenol analysis on the location og guava leaf (A3B2) 61,58 mgGAE/ 100g, high flavonoid content on the of guava leaf (A2B2) 43,69 mgQE/g, high tannin total was found in the leaf area (A3B2 ) 64.90 mg of tannic acid / kg, and high antioxidant activity (DPPH) resistance presentations were found in guava leaf (A2B2) 47.56% barrier. The preferred guava leaf tea is a powder form extraction method with 7 minutes' brewing duration, brewed with hot water (100oC), and served with warm water, yielding flavor, aroma and color with taste treatment A3B2, A2B2 aroma and A3B2 color, which has The flavor of guava leaves, a slightly spatial taste, the peculiar aroma of guava leaves and the color that produces a brownish yellow color like the tea color processed from the tea tree (Camelia sinensis). Keywords : Guava Leaf, Tatal Phenol, Flavonoid, Tanin, Antioxidant Activity.